Dual mRNA nanoparticles strategy for enhanced pancreatic cancer treatment and β-elemene combination therapy - Qianru Zhu; Chuao Yu; Yiquan Chen; Wei Luo; Meng Li; Jianhua Zou; Fan Xiao; Soohwan An; Qimanguli Saiding; Wei Tao; Na Kong; Tian Xie (Proceedings of the National Academy of Sciences, 2025)
Pancreatic ductal adenocarcinoma (PDAC) is notoriously immune-resistant, limiting the clinical efficacy of single-agent immune modulators and thereby necessitating the exploration of multimodal immunotherapy combinations. Traditional approaches combining conventional immune checkpoint inhibitors with neoantigen vaccines have shown some promise in treating PDAC but are often compromised by intratumoral T lymphocyte exhaustion and systemic toxicity. Hence, novel approaches are needed to address these challenges. Herein, we demonstrate that mRNA polymeric nanoparticles encoding anti-PD-1 antibodies in situ at the tumor site enhance the therapeutic efficacy of neoantigen-based mRNA vaccine for PDAC. This mRNA-based, in situ anti-PD-1 antibody production strategy also protects tumor-infiltrating T cells from PD-1 inhibition, potentially reducing the toxicities induced by systemic checkpoint inhibition. Our study may provide an innovative dual mRNA nanoparticle strategy for effective tumor neoantigen immunotherapy, as well as an mRNA cancer combination therapy strategy with other clinically approved drugs (e.g., β-elemene).